2015
DOI: 10.1071/fp14104
|View full text |Cite
|
Sign up to set email alerts
|

High night temperature induces contrasting responses for spikelet fertility, spikelet tissue temperature, flowering characteristics and grain quality in rice

Abstract: Climate change is increasing night temperature (NT) more than day temperature (DT) in rice-growing areas. Effects of combinations of NT (24−35°C) from microsporogenesis to anthesis at one or more DT (30 or 35°C) at anthesis on rice spikelet fertility, temperature within spikelets, flowering pattern, grain weight per panicle, amylose content and gel consistency were investigated in contrasting rice cultivars under controlled environments. Cultivars differed in spikelet fertility response to high NT, with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 43 publications
(84 reference statements)
6
48
1
Order By: Relevance
“…A clear genotypic variation even within the two gentoypes tested was seen with the fitted CP, indicating the potential of extending the introduced phenotyping technique to larger and more diverse rice panels in an attempt to identify donors with the CP occurring at a later point, to extend the predicted active grain filling duration under non-stress conditions. In addition, genotype N22, known for its reproductive-stage heat tolerance Coast et al, 2014), had minimal change in CP under HNT compared with the sensitive Gharib, supporting earlier studies that have quantified their contrasting response to heat stress. The above provides evidence for the effectiveness of the technique to study maturing rice panicles even under stress conditions.…”
Section: Discussionsupporting
confidence: 77%
“…A clear genotypic variation even within the two gentoypes tested was seen with the fitted CP, indicating the potential of extending the introduced phenotyping technique to larger and more diverse rice panels in an attempt to identify donors with the CP occurring at a later point, to extend the predicted active grain filling duration under non-stress conditions. In addition, genotype N22, known for its reproductive-stage heat tolerance Coast et al, 2014), had minimal change in CP under HNT compared with the sensitive Gharib, supporting earlier studies that have quantified their contrasting response to heat stress. The above provides evidence for the effectiveness of the technique to study maturing rice panicles even under stress conditions.…”
Section: Discussionsupporting
confidence: 77%
“…However, in our study, spikelet tissue temperature measured across all genotypes and both experiments was close to air temperature, by following an established experimental set‐up (i.e., HDT and moderately high relative humidity) wherein VPD is maintained at low levels (Jagadish et al, ; Shi et al, ). Additionally, it has been reported that the tolerant genotype with higher spikelet fertility had higher absolute spikelet tissue temperature compared to susceptible genotype (Coast, Ellis, Murdoch, Quiñones, & Jagadish, ; Shi et al, ). Our study also showed that the spikelet fertility of tolerant check N22 was much higher than that of other genotypes under high‐temperature, with no obvious difference in spikelet tissue temperature between N22 and other genotypes (Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that both the booting (10 d before heading) and heading (from heading to 10 d after) stages are extremely sensitive to heat stress [8,9]. A direct impact of heat stress during both the stages is on pollen development, pollen germination on stigma, and effective fertilization, which ultimately brings about grainless plants and yieldless crop [10,11]. As a result, heat stress during both the stages is the most damaging stress, and our study aimed to address the heat stress at the booting stage treated with 38 C/30 C (day/night) for 3 days.…”
Section: Introductionmentioning
confidence: 99%